ANALISIS BENTUK GHARAR DALAM TRANSAKSI EKONOMI - fajar, Fajar (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
Conventional financial institutions contain many elements gharar which is clearly prohibited in Islamic law. Islam has strict limits on various economic transactions, so that they are clear what is prohibited or not prohibited. Justice values ​​are a thing main principles that form the basis of economic activities, so that you feel persecuted by the other party.